Development of IKATP Ion Channel Blockers Targeting Sulfonylurea Resistant Mutant KIR6.2 Based Channels for Treating DEND Syndrome - Houtman, Marien J. C.; Friesacher, Theres; Chen, Xingyu; Zangerl-Plessl, Eva-Maria; Heyden, Marcel A. G. van der; Stary-Weinzinger, Anna (Frontiers in Pharmacology, 2022)
Introduction: DEND syndrome is a rare channelopathy characterized by a combination of developmental delay, epilepsy and severe neonatal diabetes. Gain of function mutations in the KCNJ11 gene, encoding the KIR6.2 subunit of the IKATP potassium channel, stand at the basis of most forms of DEND syndrome. In a previous search for existing drugs with the potential of targeting Cantú Syndrome, also resulting from increased IKATP, we found a set of candidate drugs that may also possess the potential to target DEND syndrome. In the current work, we combined Molecular Modelling including Molecular Dynamics simulations, with single cell patch clamp electrophysiology, in order to test the effect of selected drug candidates on the KIR6.2 WT and DEND mutant channels. Methods: Molecular dynamics simulations were performed to investigate potential drug binding sites. To conduct in vitro studies, KIR6.2 Q52R and L164P mutants were constructed. Inside/out patch clamp electrophysiology on transiently transfected HEK293T cells was performed for establishing drug-channel inhibition relationships. Results: Molecular Dynamics simulations provided insight in potential channel interaction and shed light on possible mechanisms of action of the tested drug candidates. Effective IKIR6.2/SUR2a inhibition was obtained with the pore-blocker betaxolol (IC50 values 27-37 M). Levobetaxolol effectively inhibited WT and L164P (IC50 values 22 M) and Q52R (IC50 55 M) channels. Of the SUR binding prostaglandin series, travoprost was found to be the best blocker of WT and L164P channels (IC50 2-3 M), while Q52R inhibition was 15-20% at 10 M. Conclusions: Our combination of MD and inside-out electrophysiology provides the rationale for drug mediated IKATP inhibition, and will be the basis for 1) screening of additional existing drugs for repurposing to address DEND syndrome, and 2) rationalized medicinal chemistry to improve IKATP inhibitor efficacy and specificity.